Creation and manipulation of quantum states in nanostructures - Schaffry, M (2011)
Nanostructures are promising building blocks for quantum technologies due to their reproducible nature and ability to self-assemble into complex structures. However, the need to control these nanostructures represents a key challenge. Hence, this thesis investigates the manipulation and creation of quantum states in certain nanostructures. The results of this thesis can be applied to quantum information processing and to extremely sensitive magnetic-field measurements. In the first research chapter, we propose and examine methods for entangling two (remote) nuclear spins through their mutual coupling to a transient optically excited electron spin. From our calculations we identify the specific molecular properties that permit high entangling power gates for different protocols. In the next research chapter, we investigate another method to create entanglement; this time between two remote electronic spins. This method uses a very sensitive magnetic-field sensor based on a crystal defect that allows the detection of single magnetic moments. The act of sensing the local field constitutes a two-qubit projective measurement. This entangling operation is remarkably robust to imperfections occurring in an experiment. The third research chapter presents an augmented sensor consisting of a nitrogen-vacancy centre for readout and an `amplifier' spin system that directly senses tiny local magnetic fields. Our calculations show that this hybrid structure has the potential to detect magnetic moments with a sensitivity and spatial resolution far beyond that of a sensor based on only a nitrogen-vacancy centre, and indeed this may be the physical limit for sensors of this class. Finally, the last research chapter investigates measurements of magnetic-field strength using an ensemble of spin-active molecules. Here, we describe a quantum strategy that can beat the common standard strategy. We identify the conditions for which this is possible and find that this crucially depends on the decoherence present in the system.